ARE THERE SUCH THINGS AS THEORIES OF TRAINING EQUALLY COMPARABLE TO THEORIES OF LEARNING? LITERATURE REVIEW - Fuad Cholisi (Jurnal Sosial Humaniora, 2025)
This article provides a literature review on the comparison between theories of learning and theories of training. Despite their equally vital roles in the improvement of human capital quality, it turns out that almost all of the training theories have been based, as their ground, on the learning theories. The learning theories, on the other hand, have long been established with a firm ground philosophically, psychologically, and pedagogically. This strong foundation has made learning theories such a trade mark that looks so firm, stable and reliable. As a general finding, this article concludes that there are indeed some theories of training that are applicable for individual and organizational training. However, such theories are obviously not equally comparable to the theories of learning.